Pengaruh Media Pembelajaran Power Point Pada Materi Jaringan Tegangan Rendah Terhadap Hasil Belajar Fisika Siswa - Piliang, Julia Putri; Nasution, Eni Sumanti; Siregar, Sri Utami Kholilla Mora (Yayasan Perguruan Kampus, 2023)
This research aims to determine the effect of Power Point learning media on low voltage network material (Jtr) on the learning outcomes of Class XI Science students at MAN 1 Sipirok for the 2019/2020 academic year. The type of quantitative research uses quasi-experimental research methods. The population of this study was all students at MAN 1 Siprirok consisting of 9 classes with 30 students in each class. The sample for this research was class XI MAN 1 Sipirok students with a sample size of 30 people. The sampling technique uses cluster radom sampling. The instrument uses pretest and posttest. The results of this research are that student learning outcomes using power point learning media on low voltage network material in class XI IPA MAN 1 Sipirok can be categorized as successful in improving student learning outcomes. It can be seen that the learning outcomes using Power Point learning media are better than learning media where teachers only use printed books in learning activities on low voltage network material. This research has the benefit of providing a benefit by using JTR, it will increase students' creativity and learning motivation, besides that, if the next research is carried out with a different sample, the results shown will also be different. This can be seen from the various characteristics of different students which greatly influence interest and learning outcomes.